The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1098/rspb.2008.1094
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and diversification of symbiotic trichonymphid flagellates from a common ancestor of termites and the cockroachCryptocercus

Abstract: Cryptocercus cockroaches and lower termites harbour obligate, diverse and unique symbiotic cellulolytic flagellates in their hindgut that are considered critical in the development of social behaviour in their hosts. However, there has been controversy concerning the origin of these symbiotic flagellates. Here, molecular sequences encoding small subunit rRNA and glyceraldehyde-3-phosphate dehydrogenase were identified in the symbiotic flagellates of the order Trichonymphida (phylum Parabasalia) in the gut of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 38 publications
6
77
0
Order By: Relevance
“…The presence of cellulolytic microorganisms in the hindguts of termites is one of the key events that allowed termites to thrive on nitrogenously deficient food resources (49, 63). Fossil records (80) and the similarity in gut flora and other microbial endosymbionts with those of their roach relatives (59) support the hypothesis that these associations existed in the termite ancestor (3,50,59). Termite gut symbionts reside in the lumen or are attached to the wall of the hindgut region and can represent more than 40% of the termite's weight (6).…”
mentioning
confidence: 83%
“…The presence of cellulolytic microorganisms in the hindguts of termites is one of the key events that allowed termites to thrive on nitrogenously deficient food resources (49, 63). Fossil records (80) and the similarity in gut flora and other microbial endosymbionts with those of their roach relatives (59) support the hypothesis that these associations existed in the termite ancestor (3,50,59). Termite gut symbionts reside in the lumen or are attached to the wall of the hindgut region and can represent more than 40% of the termite's weight (6).…”
mentioning
confidence: 83%
“…The protist symbionts in the hindguts of Cryptocercus cockroaches and lower termites were long suspected to have codiversified with their hosts (15,17,49). The common ancestor of Cryptocercus cockroaches and termites is thought to have evolved a dependence on a specialized consortium of gut microbes that allowed it to gain nutrition from the consumption of wood (16,50). The transmission of this gut consortium was ensured via coprophagy and by the development of proctodeal trophallaxis, which is the direct transfer of hindgut fluid from the rectum of a donor to the mouth of the recipient and dependent on some degree of social behavior in the host.…”
Section: Discussionmentioning
confidence: 99%
“…Among insects, the bacterial gut communities of termites, beetles and wood roaches have been studied extensively but the fungal communities are less well known. Most studies of gut inhabitants of wood roaches, Cryptocercus (Blattodea: Cryptocercidae), have focused on enumeration of bacteria, especially endosymbiontic bacteria, and protists without mention of fungi that may have been present (Sacchi et al 1998;Clark and Kambhampati 2003;Kitade 2004;Maekawa et al 2005;Noda et al 2006;Klass et al 2008;Berlanga et al 2009;Carpenter et al 2009;Ohkuma et al 2009;Carpenter et al 2010Carpenter et al , 2011. One study, however, reported the isolation of a yeast species from Cryptocercus punctulatus (Prillinger et al 1996, Prillinger andKö nig 2006).…”
Section: Introductionmentioning
confidence: 99%